The Effects of Progesterone on Oocyte Maturation and Embryo Development - Mojdeh Salehnia; Saeed Zavareh (International Journal of Fertility and Sterility, 2013)
Oocyte maturation and embryo development are controlled by intra-ovarian factors such as steroid hormones. Progesterone (P4) exists in the follicular fluid that contributes to normal mammalian ovarian function and has several critical functions during embryo development and implantation, including endometrial receptivity, embryonic survival during gestation and transformation of the endometrial stromal cells to decidual cells. It is well known that the physiological effects of P4 during the pre-implantation stages of some mammal’s embryos are mediated by P4 receptors and their gene expression is determined. The effects of P4 on oocytes and embryo development have been assessed by some investigations, with contradictory results. P4, a dominant steroid in follicular fluid at approximately 18 hours after the luteinizing hormone (LH ) surge may have a critical role in maturation of oocytes at the germinal stage. However, it has been shown that different concentrations of P4 could not improve in vitro maturation rates of germinal vesicles (GV) in cumulus oocyte complexes (COCs) and cumulus denuded oocytes (CDOs). Culture media supplemented with P4 significantly improved mouse embryo development. In addition, an in vivo experimental design has shown high blastocyst survival and implantation rates in P4-treated mice. In this review we explain some of the findings that pertain to the effects of P4 on oocyte maturation and embryo development both in vitro and in vivo.